SCIENTIFIC AND THEORETICAL VIEWPOINTS RELATED TO TERMINOLOGY IN LINGUISTICS - H.A.Sarimsokov (Scholar Express Journal, 2021)
This article presented theoretical approaches of the most common types of sport terms, because sport terminology spread widely and become an integral part of our modern society and very often, we do not even feel or identify them as terms. They reflect all changes happening in our life from the development of technology to the cultural and socio-political alterations. The formation of new words and word phrases according to their origin, derivation, and etymology which were surveyed by many scientists is presented in this paper. Due to different kind of examples, which were taken from a number of languages, the learners will be able to make sense the influence of new words to our current sport lexicon.
Keywords: Terminology; word; sport; fan